HUBUNGAN TINGKAT STRESS DENGAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RSUD CILILIN - Ramdhani, Yunika Salwa; Kusmiran, Eny (MAJU : Indonesian Journal of Community Empowerment, 2025)
Background: Chronic Kidney Failure is the leading cause of death in the 21st century, this disease is characterized by decreased kidney function resulting in the accumulation of metabolic waste and fluid imbalance. Hemodialysis is a palliative measure carried out for life so that significant stress arises which affects the quality of life of Hemodialysis patients. Objective: Knowing the relationship between stress level and quality of life in chronic renal failure patients undergoing hemodialysis at Cililin Hospital. Methods: This method uses a cross sectional method. This study used a total sampling technique of 33 respondents. This research instrument uses the DASS 42 questionnaire to measure stress levels and WHOQOL-BREF to measure quality of life. Bivariate analysis used chi square test to determine the relationship between variables. Results: It was found that most of the respondents were categorized as severe stress level (54.5%) and in the mild category (45.5%). Respondents who fall into the category of poor quality of life (39.4%), moderate quality of life (30.3%) and good quality of life (30.3%). The chi square test results obtained a p-value of 0.001 < 0.05. Conclusion: There is a Relationship between Stress Level and Quality of Life in Chronic Kidney Failure Patients Undergoing Hemodialysis at Cililin Hospital in 2025.